Human Endogenous Retroviral Envelope Protein Syncytin-1 and Inflammatory Abnormalities in Neuropsychological Diseases - Wang, Xiuling; Huang, Jin; Zhu, Fan (Frontiers in Psychiatry, 2018)
Human endogenous retroviruses (HERV) genome comprises approximately 8% of the human genome. Despite most of HERV genes are mutated, and cannot encode functional proteins, some HERVs genes, such as HERV-W envelope (env) glycoprotein, are known to have intact open reading frames (ORFs), which are expressed in placenta and play important roles in the function of the embryo. HERV-W env, also termed syncytin-1, has been increasingly reported to be involved in the development of schizophrenia, MS and other diseases. Our previous studies showed that syncytin-1 could induce the increase of several schizophrenia-associated genes as diverse as BDNF, NTRK2, DRD3 and GSK3β. Such over-expression of these genes might lead to neuronal dysfunctions, and contribute to the development of schizophrenia. Additionally, specific ion channels such as SK3, which is linked to the regulation of excitability, could be activated by syncytin-1. Abnormalities of these ion channels are also related to schizophrenia. More importantly, we also found that syncytin-1 could induce inflammatory. More lines of independent evidence showed that inflammatory abnormalities played a pivotal role in neuropsychological diseases such as schizophrenia and MS, while the mechanism of inflammatory abnormalities was still not well understood. In this review, we will highlight recent studies showing that syncytin-1 can elevate the expression of numerous inflammatory cytokines and cause inflammatory abnormalities in neural cells. Therefore, we might reveal a novel molecular pathogenic mechanism of syncytin-1 in neuropsychological diseases, such as schizophrenia and multiple sclerosis (MS).